(untitled) (Academicia Globe: Inderscience Research, 2023)
Being fairly a new term, the flipped classroom approach is already well-known and been put into practice by most educational institutions of the world. The technology made it impossible not to integrate itself into our classrooms. The article below discusses the origin of the flipped classroom approach and its current state in foreign language teaching.